Sequence-stratigraphic study of Cuyo Group in the Agua del Cajón Block, Neuquén Basin, Argentina. (October 2021) - Gutiérrez Pleimling, Alberto R.; Ambrosio, Alfredo; Gómez, Carlos; Bustos, Gabriela; González, José M.; Guzmán, Cecilia; Tapia, Felipe
Abstract: Agua del Cajón Block is located towards the north-east flank of the Huincul High deformation belt. The Cuyo Group, one of the main hydrocarbon targets of the block, was analyzed under the sequential-stratigraphic seismic methodology, for the purpose of establishing a genetic depositional framework that guides the development of new prospective models in the area. Ages and paleoenvironmental indicators calibration were obtained from biostratigraphic sampling. In Agua del Cajón Block, the Cuyo Group was interpreted as a second-order mesosequence, composed of eight third-order seismic sequences. Seismic-stratigraphy was integrated with the structural framework of the block, allowing an interpretation of the tectono-stratigraphic evolution of the analyzed interval. It is concluded that the development of the Cuyo Group manifests eustatic control at a second-order mesosequence scale, while at the third-order scale the sequence arrangement was modified by local tectonics. Highlights: Identification and characterization of dispositional seismic sequences in the Agua del Cajón Block. Preparation of support maps for structural sequence-analysis. Integration of seismic and exploratory wells data. Biostratigraphic sampling for age and paleoenvironmental data and integration with seismic-stratigraphic analysis. Analysis of eustatic versus tectonic control factors in the sequential arrangement.